Collaborative Communication in Sex Education: A Literature Review on Teacher-Parent Synergy in Secondary Schools - Muhammad Sodiqul Fikri; Sabila Qurrota A’yun; Nadia Putri Kamila; Tin Amalia Fitri; Amiruddin Amiruddin (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
Sex education at the junior high school level is an important aspect in shaping the character and self-awareness of adolescents regarding the biological, psychological, and social changes they experience. This study aims to examine sex education as a shared responsibility between teachers, parents, and students by highlighting effective communication patterns in its implementation. The method used is a literature review (library research) with a qualitative descriptive approach. Data was collected through a review of various journals, academic books, and recent research reports discussing sex education collaboration in schools and families. The results of the study show that open and empathetic communication between teachers, parents, and students is a key factor in the success of sex education. Teachers act as facilitators who convey scientific knowledge and moral values contextually, while parents serve as primary educators who instill moral norms and responsibilities at home. The synergy of two-way communication between schools and families has been proven to increase students' understanding of sexuality issues and reduce risky behaviour. This study emphasises that effective sex education must be designed collaboratively, be sensitive to culture and religion, and be oriented towards the formation of healthy and responsible attitudes. The findings of this study are expected to serve as a reference for the development of adaptive and sustainable sex education communication models in formal education and family environments